2015
DOI: 10.2754/avb201584020105
|View full text |Cite
|
Sign up to set email alerts
|

Papillomavirus infection of roe deer in the Czech Republic and fibropapilloma-associated levels of metallothionein, zinc, and oxidative stress

Abstract: The present study aimed at the aetiological diagnosis of skin tumours of roe deer (Capreolus capreolus) in the Czech Republic. A total of 33 roe deer specimens showing skin masses were sampled for histopathology, virus detection and identification using polymerase chain reaction (PCR) and deoxyribonucleic acid sequence (DNA) analysis, and to investigate fibropapillomaassociated levels of metallothionein, zinc and oxidative stress in 2012 and 2013. Ticks (Ixodes ricinus) and deer keds (Lipoptena cervi) were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…Both viruses have common genetic, morphological and pathogenic characteristics [127], can be disseminated by hematology pathway [28,[128][129][130][131], turning then a public health problem [132]. Moreover, BPV is considered a study prototype of oncogenic process [133].…”
Section: Oncogenic Virus and Ros Generation: A Field To Explorementioning
confidence: 99%
“…Both viruses have common genetic, morphological and pathogenic characteristics [127], can be disseminated by hematology pathway [28,[128][129][130][131], turning then a public health problem [132]. Moreover, BPV is considered a study prototype of oncogenic process [133].…”
Section: Oncogenic Virus and Ros Generation: A Field To Explorementioning
confidence: 99%
“…Furthermore, another BPV transmission pathway was described by Stocco dos Santos et al (1998), who showed the presence of BPV-2 DNA in peripheral blood and reported chromosome instability. The same authors also suggest that the peripheral blood could act as a viral disseminator (Král et al, 2015). Recent studies have reinforced the role of peripheral blood mononuclear cells (PBMCs) as virus carriers, showing that BPV is present in CD4+ and CD8+ lymphocytes (Roperto et al, 2008;Araldi et al, 2014a) and the detection of BPV activity in PBMCs by the comet assay (Araldi et al, 2013a) and flow cytometry (Roperto et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in red deer, the lesions, characteristic for cutaneous fibropapillomatosis associated with the CePV1v infections, appeared rough (with a cauliflower-like appearance), pigmented and hairless and were located in the inner hind leg or the abdominal region. According to previous reports [15][16][17]21], older roe deer appear to be more prone to disease manifestation than younger animals, while in red deer, fibropapillomas are mostly found in young animals. A similar pattern was observed in this study.…”
Section: Discussionmentioning
confidence: 90%
“…The only characterisation of the complete genome of the CcaPV-1 type belonging to the Deltapapillomavirus genus was carried out in Hungary by Erdélyi et al [20], who were the first to link the virus to the development of fibropapillomatosis in roe deer. A sporadic occurrence of fibropapillomatosis in red and roe deer was reported in Spain, France, England, Austria [16,17], the Czech Republic [21], Portugal [11] and Italy [14]. Scagliarini et al [14] were the first to publish the entire genome of a PV (CePV-1v) belonging to the Deltapapillomavirus genus in red deer with expressed clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%